X‐ray diffraction from nonuniformly stretched helical molecules. Issue 3 (18th April 2016) - Prodanovic, Momcilo; Irving, Thomas C.; Mijailovich, Srboljub M.
Abstract : A theoretical formulation for the diffraction from nonuniformly strained helical molecular assemblies is presented. The predictions of this theory are discussed in the context of double‐stranded DNA and actin filaments in the presence and absence of nonuniform strains. Abstract : The fibrous proteins in living cells are exposed to mechanical forces interacting with other subcellular structures. X‐ray fiber diffraction is often used to assess deformation and movement of these proteins, but the analysis has been limited to the theory for fibrous molecular systems that exhibit helical symmetry. However, this approach cannot adequately interpret X‐ray data from fibrous protein assemblies where the local strain varies along the fiber length owing to interactions of its molecular constituents with their binding partners. To resolve this problem a theoretical formulism has been developed for predicting the diffraction from individual helical molecular structures nonuniformly strained along their lengths. This represents a critical first step towards modeling complex dynamical systems consisting of multiple helical structures using spatially explicit, multi‐scale Monte Carlo simulations where predictions are compared with experimental data in a `forward' process to iteratively generate ever more realistic models. Here the effects of nonuniform strains and the helix length on the resulting magnitude and phase of diffraction patterns are quantitatively assessed. Examples of the predicted diffraction patterns of nonuniformly deformed double‐stranded DNA and actin filaments in contracting muscle are presented to demonstrate the feasibly of this theoretical approach.